Recentring the margins: Theorizing African capitalism after 50 years. Issue 1 (2nd January 2021) - Breckenridge, Keith; James, Deborah
Abstract: This introduction to our special issue addresses scholars' failure, in recent times, to consider and analyse the forms of capitalism that have developed on the African continent. To redress the balance, it takes up the study of economic arrangements on the continent – property, infrastructure, debt, financialization, regulation – as well as exploring the history and politics of the scholarly field of African economics as an intellectual and institutional project. In the process it considers the advantages (and drawbacks) of seeing Africa as part of the 'Global South'. Central to the special issue is the question of how to marry an analysis of intimate and smaller-scale economies centred on household, family and (often informal) labour regimes, on the one hand, with a recognition of large-scale processes such as the central banking systems imposed by states, the increasing prevalence of high-tech finance, the emergence of continent-wide regulation, and the influence of multilateral development agencies and the international publishing industry, on the other. How, we ask, can the importance of these institutions, so unlike in size and scale, be reckoned without assuming that the bigger and more powerful ones always prevail?